Internal model control (IMC) based tuning of PID controller for a non-adiabatic CSTR operating at unstable steady state - Prasad, Durga; Azmi Abu Bakar, Khairul; Kumar, Munna; Safie Mohd Satar, Nurhizam; Sriram, K.; Srivastav, Anupam; N. Upadhyay, S.; Sharan Singh, Ram (International Journal of Engineering and Technology, 2019)
A Non-adiabatic Jacketed CSTR Is known to exhibit Steady-state (output) Multiplicity, with the intermediate temperature (middle) steady-state being unstable. Since the operation of CSTR at the unstable steady state may be highly desirable (due to high productivity and safety concerns), an Internal Model Control (IMC) based technique of tuning the conventional linear Proportional Integral Derivative (PID) controller is proposed. The CSTR is analysed using a nonlinear dynamic model which is linearized around the unstable operating point based on the Taylor Series approximation, to obtain the state-space and transfer function-based model. The transfer function model of the reactor exhibits third order dynamics with one unstable pole. Both the temperature control and concentration control systems for servo and regulatory problems have been studied. The resulting IMC-PID controller has a lead-lag filter which effectively reduces the relative order of process transfer functions thereby making the process response faster. The performance of the controller is gauged by the well-established performance criteria such as the ISE, ITAE and the IAE. The system has been subjected to process uncertainties and the Simulation results verify the robustness of the proposed controller for both servo and regulatory control problems.Â Â